THE EFFECT OF CHICKEN MANURE AND COW URINE ON THE GROWTH AND PRODUCTION OF RED CHILI (Capsicum annum L) - Siswanto, Yudi; Riansyah, Riansyah; Wibowo, Fachrina (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The effect of giving chicken manure and cow urine to the growth and production of red chili (Capsicum annum L). This experiment used a factorial randomized block design (RAK), which consisted of 2 treatment factors with 16 combinations and 2 replications. The factors studied were the provision of chicken manure (R) consisting of 4 levels, namely R0 = 0 kg/m 2 , R1 = 1 kg/m 2 , R2 = 2 kg/m 2 and R3 = 3 kg/m 2 and the provision of cow urine (S) consists of 4 levels, namely S0 = 0 ml/1000 ml of water/m 2 , S1 = 100 ml/900 ml of water/m 2 , S2 = 200 ml/800 ml of water/m 2 and S3 = 300 ml/700 ml of water/m 2 . The parameters observed were plant height (cm), number of branches (branches), number of flowers (flowers), production per sample (g), production per plot (g) and production per hectare (kg). The results showed that the application of chicken manure and cow urine had an effect on the parameters of plant height (cm), number of branches (branches), number of flowers (flowers), production per sample (g), production per plot (g) and production per hectare. (kg). The interaction between chicken manure and cow urine did not affect the parameters of plant height (cm), number of branches (branches), number of flowers (flowers), production per sample (g), production per plot (g) and red chili production per hectare (kg).